Embracing Industry 4.0: Navigating the Evolution of Entrepreneurship in Romania - Grosu, Iolanda-Petronela; Rizoiu, Leonard-Alin; Dinicu, Andrei-Edward; Zhang, Xiaoliang (European Journal of Sustainable Development, 2025)
Entrepreneurship constitutes one of the oldest and most profitable occupations. It has evolved alongside the Industrial Revolutions (IR), directly influencing each other. One of the fundamental pillars of technological development is represented by inventive and innovative entrepreneurs who had the courage to investigate and implement what initially seemed to be mere dreams. The first three IRs brought major and decisive changes on a global level. The fourth revolution, called Revolution 4.0 - R 4.0 (or Industry 4.0 - I 4.0), which we consider an evolution, has brought to the forefront new fields of interest and heterogeneous areas of concern: artificial intelligence, robotics, automation, the Internet of Things, 3D printing, etc. In our research, we aimed, on the one hand, to analyze the perspective of Romanian entrepreneurs regarding IR 4.0, whether they implement measures specific to new technologies, and what the impact of these measures is. On the other hand, following the analysis of the collected data, we sought to identify possibilities for stimulating local entrepreneurship under the new R 4.0 conditions. Noting that, still, in Romania, there is insufficient investment in the necessary technological infrastructure, we began our research with a theoretical analysis of the data and the state of the specialized literature. The specific infrastructure that Romania lacks includes reliable broadband internet connectivity, advanced digital technologies such as IoT devices, and accessible automation tools. These gaps significantly hinder the ability of entrepreneurs to leverage Industry 4.0 advancements, thereby limiting their capacity to innovate and compete globally. Addressing these issues will require targeted government investments in digital infrastructure, incentives for technology adoption in key sectors, and partnerships between the private and public sectors to accelerate the deployment of Industry 4.0 technologies. In the next stage, we analyzed the data collected through a semi-structured questionnaire disseminated via crowdsourcing, to which 1026 subjects responded. Before conducting the econometric analysis of the data, three research hypotheses were formulated, which were ultimately validated. The working methodology included quantitative data analysis, descriptive statistics methods, categorical principal component analysis (CATPCA), and correspondence analysis. Data processing was performed using the IBM SPSS 20 application. A limitation of our research is that we did not select the questionnaire participants based on their competencies, allowing individuals with still limited knowledge to intuitively express opinions on a field they do not know or only think they know. The lack of competency-based selection for survey participants means that respondents may not have had the requisite knowledge to provide informed opinions, potentially skewing the results. This limitation impacts the reliability of the data and could mean that the findings are not fully reflective of expert perspectives in Industry 4.0. Future studies should consider a more rigorous selection criterion, ensuring participants possess relevant competencies. This approach would help in obtaining more accurate insights, leading to more actionable conclusions. As a future action direction, we aim to analyze the issue of local entrepreneurship by involving respondents from different professional categories who possess the necessary competencies, so that their opinions can form the basis of a more detailed analysis. This would facilitate establishing viable action directions as a basis for the sustainable and enduring development of entrepreneurship in Romania in the context of the Fourth Industrial Revolution Keywords: Entrepreneurship, Industrial Revolution, Revolution 4.0, Artificial Intelligence, Technology, Investments